16th IHIW: Immunogenetics of Aging. (9th January 2013) - Naumova, E.; Ivanova, M.; Pawelec, G.; Constantinescu, I.; Bogunia‐Kubik, K.; Lange, A.; Oguz, F.; Ozdilli, K.; Franceschi, C.; Caruso, C.; Mishra, M.; Middleton, D.
Summary Ageing is a process characterised by progressive loss of function in multiple different organ systems, such as the nervous, endocrine and immune systems. Current data showing that ageing processes may be associated with alterations in the immune system suggest that some of the genetic determinants of senescence might be polymorphic genes that regulate immune responses. The 'Immunogenetics of Aging' programme was a component introduced in the 14th International HLA and Immunogenetics Workshop (IHIWS) and developed further within the 15th and 16th. The aim of this component was to determine the contribution of immune genes to successful ageing and an increased capacity to reach the extreme limits of lifespan. Within the 16th IHIWS, new populations were included, and the number of samples analysed was increased. Analysis was focused on innate immunity genes (KIR and MBL2) and their correlation with CMV serostatus. Collaborative studies suggested that both activating and inhibitory KIR and functionally relevant MBL2 haplotypes are important factors for control of CMV infection in the elderly and therefore for chronic low‐grade inflammation. Results showed that these genes might be predictive biomarkers in ageing and longevity. Prevalence of MBL2 haplotypes determining absence of the protein (LYPB, LYQC and HYPD) was observed in elderly people with a higher CMV antibody titre. The high CMV titre was also associated with a decreased frequency of the activatory KIR2DS5 and A1B10 haplotypes in elderly. Due to the role of KIR and low or deficient MBL haplotypes in viral infections, these genetic markers could be considered as indicators of a need for CMV prophylaxis at younger age and therefore increased probability of longer lifespan.